Privacy Mechanism of Communal Housing in Surabaya - Inunk Marufa; Happy Ratna Santosa; Arina Hayati (IPTEK Journal of Proceedings Series, 2020)
Social interaction in housing and settlements affects the achievement of individual privacy need. Social interaction and privacy are two concepts that are equally important in achieving the sustainable housing concept. Moreover, between both must be balanced that daily living activities can be expressed equally. This paper is focused on the analysis of spatial privacy mechanisms in housing with communal culture, where there are high social values. This study is conducted in the natural setting by using qualitative design research. Data collection is used in several tactics. Firstly, using theoritical review, the model of privacy mechanism by Altman (1980) is used as the core of theory. Then, the theory is tested in specific case study, which is using non-participatory observation by observing the activities of participants in several times. Secondly, through participatory observation with in-depth interviews, the perceptions of privacy are explored to reveal specific expression of privacy mechanism in spatial arrangement. This result shows that cultural aspect is closely related to the participant's personality in managing his privacy needs. High social value in communal housing causes individuals to have verbal and non-verbal privacy mechanisms by considering community groups. Then, environmental mechanism obtained by creating a private space in social spaces.